FREQUENCY OF DOUBLE EXPRESSOR LYMPHOMA IN A TERTIARY CARE HOSPITAL - Hassan, Masroor; Khattak, Maria Tasneem; Qamar, Muhammad Ashraf; Javed, Sarah; Saeed, Syeda Uzma (Journal of Ayub Medical College Abbottabad, 2021)
Background: Accounting for 30% cases of all lymphoid neoplasms, Diffuse large B cell lymphoma (DLBCL) is the commonest lymphoma worldwide. It occurs over a wide age range and has diverse morphology, immunophenotype and clinical outcome. Objectives of the study were to determine the frequency of Double expressor lymphoma (DEL) in a tertiary care hospital. Methods: This descriptive cross-sectional study was carried out in the Department of Histopathology, Rehman Medical Institute Peshawar from June 1st to December 1st, 2018. A total of 88 newly diagnosed cases of diffuse large B-cell lymphoma (DLBCL); diagnosed on incisional or excisional biopsies were included in the study by non-probability consecutive sampling. Statistical analysis was carried out using SPSS-23. Quantitative variables were calculated as mean±SD. Qualitative variables were computed as frequency and percentages. Post stratification chi-square test was applied keeping p value equal or less than 0.05 as significance. Results: In our 88 cases of DLBCL, 56 (63.6%) were males and 32 (36.4%) were females. Age of patients ranged from 15yrs to 84yrs. Mean age was 50.8±15.2SD. Activated B-cell like (ABC) subtype of DLBCL constitute 51 cases (58%) while 37 cases (42%) were of germinal centre B-cell like (GCB) subtype. Nineteen cases (21.6%) were of DEL. Cervical node was the commonest site of involvement (n=17, 19.3%) followed by stomach (n=10, 11.4%) and tonsil (n=6, 6.8%). Out of 19 cases of DEL, 17 cases (89.5%) were of ABC type. DEL was found to have significant correlation with ABC subtype of DLBCL (p=0.002). DEL had no correlation with gender (p=0.6), age (p=0.27), Mib-1 (p=0.36) and tumour site (p=0.42). Conclusion: The frequency of DEL in our study was 21.6% which is comparable to other studies who used similar cut-offs for c-Myc and BCL2 and similar criteria of inclusion as in our study. Significant association was found between DEL and ABC subtype of DLBCL. Keywords: Double protein lymphoma; Double expressor lymphoma; Diffuse large B cell lymphoma; Double hit lymphoma, Frequency